Photocatalytic degradation of Brilliant Green and Acid Orange 7 in single and binary solution using TiO2 as catalyst - Noor Ilya, Kosmadi (Universiti Malaysia Perlis (UniMAP), 2013)
Access is limited to UniMAP community.